REKONSEPTUALISASI KONSTRUK KUALITAS LAYANAN SPESIFIK PADA KONTEKS PERGURUAN TINGGI - Fachri Eka Saputra (Management Insight: Jurnal Ilmiah Manajemen, 2020)
This study aims to reexamine the scale of service quality measurement that refers to multi-dimensional concepts. This type of research is quantitative descriptive research. This research is a quantitative research. Sampling in this study was carried out randomly by using probability sampling with a stratified random sampling technique in obtaining information from respondents. The number of samples used was 200 people in each department in the Economic and Business Faculty, University of Bengkulu. The results showed that service quality can be classified into 6 factors. These factors consist of Factor 1 which focuses on administrative services; Factor 2 which focuses on facilities and infrastructure; Factor 3 which focuses on the quality of teaching; Factor 4, which focuses on resource allocation; Factor 5, which focuses on the ease of borrowing space; and Factor 6 focuses on lecturer responsiveness to student complaints. The higher education institution and each unit under it are expected to pay attention to these factors in developing policies and programs.  Keyword:   Service Quality, HEdPerf (Higher Education Performance), HiEdQual (Higher Education Quality), Higher Education Institution.